2011
DOI: 10.1007/s00068-011-0081-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of blowout fractures of the orbital floor reconstructed with a polyglactin 910/PDS implant

Abstract: Reconstructive surgery of the orbit is one of the most demanding challenges in maxillofacial surgery. For traumatic defects of the orbital floor, reconstruction using a polyglactin 910/PDS implant (Ethisorb(™)) seems to be a reliable method for the repair of small-to-moderate defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…and presented no correlation to long-term complications. Similar results were presented with ethisorb patches – which are used off-label - as covering material in the study of Jank et al 25 and Blake et al 26 A recent study from Ramphul and Hoffmann 3 found no significant association of other used materials (titanium mesh, Medpor, a combination of Medpor and mesh, and gelatin film) and diplopia in their study, too. Compared to titanium implants our results showed a slightly better outcome ranging between 24.6 and 29.8% 27 …”
Section: Discussionsupporting
confidence: 75%
“…and presented no correlation to long-term complications. Similar results were presented with ethisorb patches – which are used off-label - as covering material in the study of Jank et al 25 and Blake et al 26 A recent study from Ramphul and Hoffmann 3 found no significant association of other used materials (titanium mesh, Medpor, a combination of Medpor and mesh, and gelatin film) and diplopia in their study, too. Compared to titanium implants our results showed a slightly better outcome ranging between 24.6 and 29.8% 27 …”
Section: Discussionsupporting
confidence: 75%
“…28 As a material, PDS has been used successfully in orbital floor reconstruction and has shown excellent long-term results over 15 years. 29 The biologic properties of PDS showed that the degradation products of the synthetic aliphatic polymer simulate the regeneration of bone by their osteoconductive properties. 9 This early bony regeneration at the area of the skull base was identified on the postoperative CT imaging of our patient in case B.…”
Section: Discussionmentioning
confidence: 99%
“…Polyglactin 910/polydioxanone (Ethisorb ® ) is a well-known material in neurosurgery, primarily used to repair dura mater defects. Apart from this main indication, it has also been used for OFF repair since many years, and this "off-label" use was reported in several studies [22][23][24][25]. In many aspects, Ethisorb ® represents a highly suitable material to restore proper anatomical outlines in the delicate area of the orbital floor.…”
Section: Discussionmentioning
confidence: 99%
“…Ethisorb ® was originally described as an alloplastic material suitable for closure of dura mater defects in neurosurgery [19,20] and has proven to be of great value in this indication [21]. However, off-label use of this material for the repair of OFFs has been described, too [22][23][24][25]. With regard to the fact that this material is not licensed for the use in orbital surgery it was the aim of our retrospective clinical study to further assess its value in OFF repair with a focus on ophthalmologic outcome.…”
Section: Introductionmentioning
confidence: 99%